Phase and Texture Evolution in Chemically Derived PZT Thin Films on Pt Substrates. Issue 9 (7th June 2014) - Mhin, Sungwook; Nittala, Krishna; Lee, Jinhyung; Robinson, Douglas S.; Ihlefeld, Jon F.; Brennecka, Geoff L.; Sanchez, Luz M.; Polcawich, Ronald G.; Jones, Jacob L.; Alford, N.
<x xml:space="preserve">Abstract</x> The crystallization of lead zirconate titanate (PZT) thin films was evaluated on two different platinum‐coated Si substrates. One substrate consisted of a Pt coating on a Ti adhesion layer, whereas the other consisted of a Pt coating on a TiO2 adhesion layer. The Pt deposited on TiO2 exhibited a higher degree of preferred orientation than the Pt deposited on Ti (as measured by the Full Width at Half Maximum of the 111 peak about the sample normal). PZT thin films with a nominal Zr/Ti ratio of 52/48 were deposited on the substrates using the inverted mixing order (IMO) route. Phase and texture evolution of the thin films were monitored during crystallization using in situ X‐ray diffraction at a synchrotron source. The intensity of the Pt3Pb phase indicated that deposition on a highly oriented Pt/TiO2 substrate resulted in less diffusion of Pb into the substrate relative to films deposited on Pt/Ti. There was also no evidence of the pyrochlore phase influencing texture evolution. The results suggest that PZT nucleates directly on Pt, which explains the observation of a more highly oriented 111 texture of PZT on the Pt/TiO2 substrate than on the Pt/Ti substrate.